Seasonal Changes in the Vertical Distribution of Rotifers in a Eutrophic Shallow Lake with Contrasting States of Clear and Turbid Water - Claps, María Cristina (2011)
Monthly zooplankton samples were taken from a shallow Argentinean lake in 1997- 1998, and spatiotemporal changes in rotifers in the water column were examined. The most abundant and frequent species were Brachionus calyciflorus, B. caudatus, B. havanaensis, Keratella tropica, Filinia longiseta, and Polyarthra vulgaris. These perennial species are considered to be common in eutrophic waters, are eurytopic, and are widely distributed. The phytoplankton composition, competition for food with other grazers, and predation pressure, plus the occurrence of different periods including a turbid phase, a phase with coverage of submerged macrophytes (Potamogeton pectinatus), and a flooding phase, defined the annual planktonic rotifer succession in the lake. Small-scale vertical distributions of rotifers in this homothermal lake were related to both biotic and abiotic forces. The presence of macrophytes favored an increase in planktonic-rotifer densities along with a specific richness associated with the possibility of refuge, the incorporation of littoral species, and food diversification.